Peran Dinas Perhubungan Provinsi Jawa Timur dalam Peningkatan Kualitas Pelayanan Angkutan Umum Transportasi Bus Antar Kota dalam Provinsi (AKDP) - Amalia Indah Savitri; Debby Febriyan Eprilianto; Muhammad Farid Ma’ruf; Revienda Anita Fitrie (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
This study aims to analyse the role of the East Java Provincial Transportation Agency in improving the quality of inter-city bus transportation services within the province (AKDP) based on Soekanto's role theory (in Solahudin et al, 2022), which is reviewed using three indicators: regulatory role, service role, and supervisory role. The research employed a qualitative research method with techniques of interviews, observation, and documentation of the Transportation Agency, Organda, PO owners, drivers and conductors, as well as passengers at Bungurasih Terminal. The results of the study show that in terms of regulation, the Transportation Agency has established tariff policies and Minimum Service Standards (SPM), but these have not functioned optimally as operational guidelines, as reflected in the low transparency of tariff information and the varying quality of the fleet. In terms of service, although safety inspection procedures and service facilities are available, the quality of safety, comfort, terminal facilities, as well as access to information and complaint mechanisms have not been consistently felt by users. In terms of supervision, tariff compliance control and SPM implementation remain weak and tend to be tolerant of irregularities. The main findings indicate a serious gap between normative standards and field practices, resulting in standards losing their coercive power as quality guarantors. Therefore, this study recommends strengthening the enforcement of standards in a firm and consistent manner, increasing the transparency of service and tariff information, and conducting supervision that is oriented towards tangible results for the community.